ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SEKOLAH MENENGAH ATAS NEGERI 3 MATARAM - I Wayan Rudiarta; Sintia, Ni Kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Abstract This research was conducted to analyze the use of learning media in the subjects of Hindu Religious Education and Ethics at SMA Negeri 3 Mataram. Hinduism and Ethics Education is a compulsory subject in the world of education in Indonesia. Through these subjects, students are formed and directed to practice the teachings of Hinduism. However, students often feel bored, sleepy, and difficult to understand the material so that learning activities cannot take place properly and cannot achieve learning goals. The existence of learning media is expected to be a mediator and tool for students and teachers in the learning process so that learning activities can be effective and streamlined and learning objectives can be achieved. However, in several previous studies, the functions and benefits of media in learning could not be fulfilled so that the use of learning media was analyzed by researchers. This research is a qualitative research that uses data collection methods in the form of direct non-participant observation, structured direct interviews, and documentation. In this study, data analysis was carried out by reducing data, presenting data, and drawing conclusions. Based on the results of data analysis, it is concluded that the existence of learning media can support learning success. Media makes the learning process more interesting, more effective and efficient, and more interactive, making students enthusiastic and enthusiastic in participating in learning activities and making it easier for students to understand the material being taught. Although the existence of the media has not been able to make students always spirit, enthusiastic, focused in the future and actively asking questions.